PENGARUH PERBEDAAN LAJU WAKTU PROSES PEMBEKUAN HASIL COR ALUMINIUM 319 DENGAN CETAKAN LOGAM TERHADAP STRUKTUR MIKRO DAN SIFAT MEKANIS - Errens Lowther; Sofyan Djamil; Eddy S Sirdj (Program Studi Teknik Mesin Universitas Tarumanagara, 2017)
Abstract: Aluminum alloy is a raw material in industry. Aluminum alloy used is aluminum alloy aluminum alloy 319. Materials were investigated to obtain aluminum alloys that have strong mechanical properties of the difference in the rate of clotting. Research 319 aluminum alloy was investigated by conducting the smelting process in the crank case and printed materials by using metal molds, then do differences in rates of freezing process with an open-air media, media dry sand and wet sand media as a medium deceleration. The next step is testing using tensile testing, testing, hardness with Brinell method, and metallography. From the results, with the help of wet sand media has a hardness of 68 BHN and the UTS 241.89 MPa, for open air medium hardness of 62 BHN and the UTS 224.03 MPa and dry sand media assistance hardness of 54 BHN and the UTS 190.9 MPa.